Multiple regression analysis for predicting few water quality parameters at unmonitored sub-watershed outlets in the St. Joseph River basin, USA. Issue 25 (13th December 2022) - Babbar, Richa; Chaubey, Indrajeet
Abstract: In this study, six multiple regression models were tested for predicting water quality during spring and fall seasons at unmonitored sites within St. Joseph River basin, USA. A relationship between a total of 28 independent features that were derived from land use, morphology and water balance parameters was established with the known water quality at the specified monitoring sites along the River. Each model was tested, trained and cross validated for their prediction efficacy. The results indicated that ridge regressor best predicted the nonpoint water quality parameters during both the seasons. The results were validated for one sub-watershed outlet. A relative error was found to be low but relatively higher during fall season compared to spring season. The usefulness of this study lies in populating river monitoring program with water quality data from unmonitored sites, and thus, be made available for modelling and developing management strategies.